2005
DOI: 10.3748/wjg.v11.i42.6624
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile in Egyptian hepatitis C virus genotype-4 in relation to liver disease progression

Abstract: Liver disease progression from CLD to HCC due to HCV genotype-4 infection is associated with an imbalance between Th1 and Th2 cytokines. IL-2R, TNF-RI, and TNF-RII could be used as potential markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 30 publications
6
48
2
1
Order By: Relevance
“…Interestingly, our data demonstrated an increased frequency of IL-6, IL-10 and IL-12 producers in RIBA-POS blood donors, similar to that observed in the viremic group. The increased frequency of high IL-6 and IL-10 producers in these subjects is similar to reports examining chronically infected HCV patients [33,34] . Since cytokine genes are polymorphic, and certain mutations located within coding/regulatory regions have been shown to affect the overall expression and secretion of cytokines, there may be a correlation between cytokine gene polymorphisms and their association with the outcome of HCV infection.…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, our data demonstrated an increased frequency of IL-6, IL-10 and IL-12 producers in RIBA-POS blood donors, similar to that observed in the viremic group. The increased frequency of high IL-6 and IL-10 producers in these subjects is similar to reports examining chronically infected HCV patients [33,34] . Since cytokine genes are polymorphic, and certain mutations located within coding/regulatory regions have been shown to affect the overall expression and secretion of cytokines, there may be a correlation between cytokine gene polymorphisms and their association with the outcome of HCV infection.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, the levels of the TNF-αRs, TNF-αRI and TNF-αRII, were higher in HCC patients when compared with healthy individuals (162). However, in other studies, TNF-α levels were lower in HCC tumor tissue versus the tissue surrounding the tumor and in HCC patients versus healthy individuals (163,164). In a study by Kakumu et al TNF-αRs correlated with disease progression and IFN-α treatment did not affect their level (162).…”
Section: Hepatic Stellate Cells (Hscs)mentioning
confidence: 90%
“…Several groups have shown that IL-10 is highly expressed in HCC tumors and individuals with HCC versus non-tumorous-surrounding tissue controls or healthy cohorts (162,164,(173)(174)(175). These studies suggest that increases in IL-10 and perhaps other Th2 cytokines correlate with progression.…”
Section: Hepatic Stellate Cells (Hscs)mentioning
confidence: 97%
“…Differences among HCV genotypes in geographic distributions have provided investigators with an epidemiologic marker that can be used to trace the source of HCV infection in a given population 5 . Hepatitis C virus genotypes and subtypes determination is an important factor in the pretreatment evaluation of the patients and in defining better treatment strategies 18 .…”
Section: Discussionmentioning
confidence: 99%